Jordanian EFL Supervisors' Perspectives towards EFL Teachers' Using Authentic Assessment Strategies and Tools - Ahmad Muhammad Yousuf Al-Zawahrah (Deanship of Scientific Research (DSR), the University of Jordan, 2024)
Objectives: The current study aimed to explore the perspectives of English language supervisors in the Hashemite Kingdom of Jordan regarding the extent to which English as a Foreign Language (EFL) teachers in government schools practice authentic assessment strategies and tools. Additionally, the researcher attempted to uncover the challenges faced by EFL teachers in using authentic assessment strategies and tools.. Methods: For this study, the researcher followed a hybrid approach, constructing a questionnaire distributed to English language supervisors, totaling 102, supplemented by interviews with 10 selected supervisors based on accessibility.  Results: Statistical results revealed that pen-and-paper and observation-based assessment strategies were the most commonly used and applied by English language teachers, while self-assessment strategy was the least used according to supervisors' perspectives. The study also showed that checklist and rubric were the most commonly used authentic assessment tools. Moreover, the study indicated a strong gender effect on the use of authentic assessment strategies and tools in favor of females. The study identified several challenges hindering the use of authentic assessment strategies and tools, revolving around three main axes: students' proficiency level, infrastructure, and teachers' readiness in terms of attitude, skills, and knowledge. Conclusions: The researcher recommends designing an educational program on authentic assessment strategies and tools with a focus on practical aspects and implementing it through a series of face-to-face workshops at the school network level to refine the skills of English language teachers in the field of authentic assessment, especially in boys' schools.